2008
DOI: 10.1177/154193120805200433
|View full text |Cite
|
Sign up to set email alerts
|

Screening Enhancements: Why don't they Enhance Performance?

Abstract: Data obtained utilizing image enhancements in a carry-on bag x-ray screening task were analyzed to determine whether and how image enhancements affect performance. To complement earlier studies of experienced screeners, sixty-six novices to the screening task used six different overall enhancements. Results indicated a significant worsening of performance, A', between Original images and Negative images, but no performance differences for the other enhancements, similar to effects found for experienced screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Participants are shown x-ray images of passengers’ carry-on baggage on actual x-ray systems or standard computer monitors. They are required to search images—20% to 50% of which typically contain threat objects—and then decide if a threat is present or not (e.g., Ghylin et al, 2008; Liu & Gale, 2011; McCarley et al, 2004; Schwaninger & Wales, 2009). Signal detection measures of sensitivity ( d ′, A ′) and bias ( c, B ″) are often used as dependent variables to measure detection performance (Wales et al, 2009), and are considered reliable for this purpose (Hofer & Schwaninger, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants are shown x-ray images of passengers’ carry-on baggage on actual x-ray systems or standard computer monitors. They are required to search images—20% to 50% of which typically contain threat objects—and then decide if a threat is present or not (e.g., Ghylin et al, 2008; Liu & Gale, 2011; McCarley et al, 2004; Schwaninger & Wales, 2009). Signal detection measures of sensitivity ( d ′, A ′) and bias ( c, B ″) are often used as dependent variables to measure detection performance (Wales et al, 2009), and are considered reliable for this purpose (Hofer & Schwaninger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies found that IEFs provide no significant improvements in detection performance compared with the standard color view. Indeed, in some cases, IEFs decreased performance (Ghylin et al, 2008; Klock, 2005; Michel, Koller, Ruh, & Schwaninger, 2006).…”
Section: Introductionmentioning
confidence: 99%